Regulatory Influences on Environmental Protection: Why Shipping Companies Comply and When They Don't. (3rd April 2017) - Akamangwa, Ngwatung
ABSTRACT: This article reports the findings of an empirical study on the regulation of ship-source pollution at one United Kingdom-based global ship management company. In examining the corporate response of the case-study company, particular attention is given to the regulatory influences promoting such compliance as expressed in the views of company executives. The findings show that both legal regulatory pressures and customer demands are important factors in encouraging the company to comply with environmental requirements. However, the study also revealed that compliance with environmental requirements ultimately depends on the way in which individual companies adapt to different national regulatory and enforcement regimes.